Comparison of the grain growth behavior and defect structures of flash sintered ZnO with and without controlled current ramp. (15th March 2019) - Phuah, Xin Li; Wang, Han; Charalambous, Harry; Jha, Shikhar Krishn; Tsakalakos, Thomas; Zhang, Xinghang; Wang, Haiyan
Abstract: During the flash sintering of ceramics, rapid densification occurs during the non-linear increase in current. To investigate the effect of an abrupt increase in current, a detailed microstructure characterization of flash sintered ZnO samples has been conducted and compared to a sample with controlled current ramp (i.e., linear increase of current). It has been found that the rapid densification during flash sintering limits the grain growth leading to finer grain sizes compared to the sample with a controlled current ramp. Stacking faults have been observed in the microstructure of both samples due to the generation of point defects. Graphical abstract: Unlabelled Image